2021
DOI: 10.3389/fonc.2021.731547
|View full text |Cite
|
Sign up to set email alerts
|

ASF1B Promotes Oncogenesis in Lung Adenocarcinoma and Other Cancer Types

Abstract: Anti-silencing function 1B histone chaperone (ASF1B) is known to be an important modulator of oncogenic processes, yet its role in lung adenocarcinoma (LUAD) remains to be defined. In this study, an integrated assessment of The Cancer Genome Atlas (TCGA) and genotype-tissue expression (GTEx) datasets revealed the overexpression of ASF1B in all analyzed cancer types other than LAML. Genetic, epigenetic, microsatellite instability (MSI), and tumor mutational burden (TMB) analysis showed that ASF1B was regulated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 81 publications
3
11
0
Order By: Relevance
“…As one of histone H3-H4 chaperone anti-silencing function 1 (ASF1) isoforms, ASF1B plays important roles in chromatin-based progression of cellular DNA replication and transcription regulation, especially in cell proliferation ( Paul et al, 2016 ). Accumulating evidence has shown that up-regulation of ASF1B stimulated cancer cell proliferation, DNA replication and migration, accompanied by restrained cell cycle arrest and apoptosis ( Misiewicz-Krzeminska et al, 2013 ; Han et al, 2018 ; Zhou et al, 2019 ; Liu X. et al, 2020 ; Zhang et al, 2021 ), which was also consistent with our enrichment analysis of module genes ( Figure 2A ). In addition, several studies have underlined the important prognostic impact of ASF1B on a variety of cancers ( Corpet et al, 2011 ; Chen Z. et al, 2021 ; Feng et al, 2021 ).…”
Section: Resultssupporting
confidence: 90%
“…As one of histone H3-H4 chaperone anti-silencing function 1 (ASF1) isoforms, ASF1B plays important roles in chromatin-based progression of cellular DNA replication and transcription regulation, especially in cell proliferation ( Paul et al, 2016 ). Accumulating evidence has shown that up-regulation of ASF1B stimulated cancer cell proliferation, DNA replication and migration, accompanied by restrained cell cycle arrest and apoptosis ( Misiewicz-Krzeminska et al, 2013 ; Han et al, 2018 ; Zhou et al, 2019 ; Liu X. et al, 2020 ; Zhang et al, 2021 ), which was also consistent with our enrichment analysis of module genes ( Figure 2A ). In addition, several studies have underlined the important prognostic impact of ASF1B on a variety of cancers ( Corpet et al, 2011 ; Chen Z. et al, 2021 ; Feng et al, 2021 ).…”
Section: Resultssupporting
confidence: 90%
“…In this research, we used bioinformatics and multiple databases to comprehensively analyze the expression of ASF1B in pan-cancer, and found that ASF1B was abnormally expressed in most cancers, including liver cancer, which is consistent with current literature reports ( 27 29 ). In order to explore the relationship between ASF1B and HCC in detail, RNA-seq data and corresponding clinical data of HCC in TCGA were analyzed separately.…”
Section: Discussionsupporting
confidence: 85%
“…More importantly, the expression levels of ASF1B were reported to be associated with TME in STAD ( Rossetti and Sacchi, 2020 ). From a mechanistic point of view, ASF1B indirectly regulated CKS1B to mediate growth, apoptosis, and cell cycle progression in cancers ( Zhang et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%